Pengaruh jarak nozzle penyemprot terhadap kemampukerasan baja komersil dengan metode jominy test - Yusuf Yusuf; Asep Ruchiyat; Muh Anhar (Universitas Muhammadiyah Metro, 2020)
Steel is the material most widely used in the industry. To avoid wear and tear on steel, it is necessary to do heat treatment to improve the mechanical properties of the steel according to its application in the field. The increase in hardenability in metals can be determined by doing a hardenability test, namely the Jominy test method. The Jominy test is a method to determine the hardness value of metal using ASTM standards. This research was conducted with varying the distance of the nozzle of the sprayer to the lower end of the specimen, namely 10 mm, 12.5 mm, and 14 mm with a long spraying time of 15 minutes. The heat treatment process at temperature of 780oC and 90 minutes holding time. The averagehardness value of specimen number one (10 mm spraying distance) is 45.43 kgf, specimen number two (12.5 mm spraying distance) is 45.68 kgf, and specimen number three (14 mm spraying distance) is 44.31 kgf. The highest hardness value was specimen number two, there was an increase of 1.87 kgf (4.02%), according to ASTM standards where the spraying distance was 12.5 mm.Keywords: Steel, spraying distance, Jominy test.